Failure analysis of a welded steel pipe at Kullar fault crossing. (January 2017) - Kaya, Ercan Serif; Uckan, Eren; O'Rourke, Michael J.; Karamanos, Spyros A.; Akbas, Bulent; Cakir, Ferit; Cheng, Yin
Abstract: The seismic response of a 2200-mm-diameter welded steel pipe at strike slip Kullar fault crossing in Izmit, Kocaeli during 1999 Kocaeli earthquake is investigated. The pipe was crossing the fault-line with an angle of 55° and suffered leaks due to 3.0 m of right lateral movement of fault, which imposed compressive axial strain in the pipe. The backfill material of the trench was native soil which was non-homogenous (soft and stiff clay) with respect to fault line-soft material on the North side, stiff material on the South side. Field observations revealed two major wrinkles with finger width cracks and a minor wrinkle on the soft soil side of the fault. Large plastic strains and local folding were observed at wrinkles due to compressive strains. The case is known as one of the best documented fault crossing examples. The failure behavior of the Thames water pipe during 1999 Kocaeli earthquake is simulated by utilizing a 3D nonlinear continuum FE model. The numerical model considers contact surface at soil pipe interface and performs large deformation analyses of the pipe. The locations of wrinkles as well as axial displacements/rotations demands due to fault rupture are predicted. It is observed that once wrinkle initiates, strain in the pipe away from the wrinkle reduces after initial local buckling and additional shortening of the pipeline tends to accumulate at the wrinkle causing large plastic strains and rotation demands associated with fault rupture, an observation consistent with field observations and 2005 ALA guidelines. Highlights: The main highlights of this research are to investigate the response of Thames water pipeline by utilizing a full three dimensional (3D) nonlinear continuum model. to investigate the nonlinear behavior of wrinkles in the post elastic phase of steel pipe which is subjected to net compression. to simulate pipe internal pressure and free, fixed and flexible (equivalent boundary spring) pipe end boundary conditions.